Application of the X-ray densitometry in the evaluation of the quality and mechanical properties of biomass pellets - Tomazello-Filho, Mario; Valaert, Jorre; Tenorio-Monge, Carolina; Moya-Roque, Róger (Elsevier, 2015)
The use of the X-ray technique and the X-ray densitometry to determine pellet particle distribution and to understand the biomass compaction and its effects in pellet properties has been limited. The present work evaluates the quality of pellets manufactured with several lignocellulosic materials by using X-ray photography for studying surface cracks and irregularities, and by using X-ray densitometry to evaluate density and its variation in longitudinal and transversal directions. Density values and their variation were correlated to the pellets' mechanical properties (mechanical durability and compression resistance). It was found that X-ray photography may be applied to evaluate the presence of cracks and irregularities in the pellets' surface; however, these are not indicators of pellet durability or compression resistance. Moreover, density evaluation by the X-ray densitometry technique allowed the determination of the pellets' mechanical resistance and durability. A negative correlation was observed between the force at break and the coefficient of variation of density. No correlation was found between the mechanical durability and the average density or its variation. According to the above results, X-ray technique can be utilized to study the pellet quality.
https://www.scopus.com/inward/record.url?eid=2-s2.0-84922232547&partnerID=40&md5=5d8df1d4b8ac23dc641702d585cfb57d
Keywords: Densidad; Durabilidad; Propiedades mecánicas; Fotografía; Rayos X; Research Subject Categories::TECHNOLOGY::Materials science